As estratégias de luta pela liberdade nos últimos anos da escravidão na vila/cidade de Bananeiras-PB (1871-1888) - Oliveira, Daniel de (2017)
The present work analyzed the strategies experienced by the slaves in the struggle for the conquest of freedom in the last years of slavery in the town / town of Bananeiras-PB (1871-1888). Among the various forms seized as a mechanism to seek freedom, we perceived that the fugues and the actions of freedom were some instruments used, but it was found that freedom, in some cases, in which they involved freedmen, there was judicial questioning about the supposed freedom. In order to achieve these results, our study relied on a number of documents, in particular the Judiciary. The most important were: postmortem inventories, lists of registrations, lawsuits and petitions for liberty, maintenance of liberty, 19th century legislation Law 2040 of September 28, 1871, Decree 4835 of December 1, 1871 and Decree November 13, 1871), baptismal seats, Province President's Report, Newspapers and petitions for the sale of slaves. To make a comparison of these sources we use the methodological contributions of the social historiography of slavery and the English historian Edward Palmer Thompson, particularly the concept of resistance. Some of the methodologies that I tried to practice were the nominative link and the historical demography that allowed to create a profile of the Bananeiras slave population in the last years of the slavery, as well as to trace some histories of lives of captive people demonstrating their performances as historical subjects. The Research Line that this dissertation is linked to is History Teaching and Historical Knowledge. The justification for this line is that this dissertation brings several positive representations for the black population, as well as, possibilities for History Teaching as required by Federal Law 10.639 / 03.